Primary anterior urethral diverticulum - Sailukar M; Parikh K; Phadke V; Chakrabarti N (Wolters Kluwer Medknow Publications, 2007)
Congenital diverticulum of the anterior urethra in male is uncommon and typically occurs at the penoscrotal junction. This is a report of a large primary diverticulum in the anterior urethra in a 4-year-old male child who was successfully treated with diverticulectomy and urethroplasty.